The Role of the Indonesian Attorney General's Office in Capital Market Law Enforcement (a Case Study of PT Asuransi Jiwasraya) - Iddo Andua Ramadhan; Sri Wahyu Handayani; Abdul Aziz Nasihuddin (CV Edujavare Publishing, 2026)
The capital market serves as a strategic instrument in national economic development, acting as a vehicle for fund mobilization and investment. However, the complexity of transactions within the capital market sector also creates opportunities for financial crimes that result in state financial losses and diminished investor confidence. One of the most significant cases involves corruption at PT. Asuransi Jiwasraya (Persero), characterized by the misuse of investments through capital market instruments. This study aims to analyze the authority and role of the Indonesian Attorney General's Office (Kejaksaan RI) in capital market law enforcement and to examine its implementation in handling the PT. Asuransi Jiwasraya case. The study employs a normative legal research method, utilizing statutory, conceptual, and case-based approaches. Legal materials were gathered through a literature review comprising primary, secondary, and tertiary sources and analyzed qualitatively using a descriptive-prescriptive method and deductive reasoning. The findings indicate that the Indonesian Attorney General's Office possesses strategic authority as “dominus litis” within the criminal justice system to investigate and prosecute corruption crimes related to the capital market sector, provided the element of state financial loss is established. In the PT. Asuransi Jiwasraya case, the Office successfully proved the abuse of authority, investment manipulation, and state financial losses amounting to IDR 16.81 trillion; it also applied corporate criminal liability and utilized